Characterization and ex vivo expansion of rare in situ cytokine secreting T cell populations from tumor tissue and blood of oral squamous cell carcinoma patients - Stamova, Slava; Ott-Rotzer, Birgitta; Smetak, Heiko; Schaeffler, Katharina; Eder, Ruediger; Fink, Irina; Hoffmann, Petra; Reichert, Torsten E.; Beckhove, Philipp; Spanier, Gerrit (Journal of Immunological Methods, 2021)
Rare subpopulations of tumor antigen-reactive memory T cells, which actively secrete type-1 effector cytokines, particularly TNF-α in situ, possess anti-tumor activity and prognostic relevance. These cells are relevant for cancer immunotherapy; however, their low frequencies make them difficult to study and novel protocols for their culture and expansion ex vivo are needed. Here, we studied the presence of T cells secreting type-1 cytokines (Cy+T cells) in the blood and tumors of 24 patients with oral squamous cell carcinomas (OSCC) and explored possibilities for their isolation and expansion. More than 90% of OSCC patients contained enriched numbers Cy+T cells in the blood and tumors compared to healthy donors in which these were hardly detectable. The majority of TNF-α+T cells were CD4+ T helper cells while IFN-γ+TIL were predominantly CD8+. Cy+T helper cells in the blood were early-differentiated memory T cells while Cy+TIL and Cy+CD8+T cells showed advanced-differentiated memory T cell phenotypes. We explored different conditions for their in vitro culture and found that Cy+T cells can be efficiently expanded in vitro to similar levels as Cy−T cells and after expansion maintained their TNF-α secreting capacity. However, for optimal expansion they required specific culture conditions to support the maintenance of stem-like and central memory T cell phenotype. In conclusion, we show that Cy+T cells are enriched in OSCC patients and report a novel cell culture protocol optimized to specifically expand and functionally maintain these cells for further functional characterization or for their exploitation in immunotherapy of OSCC.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Immunotherapy; OSCC; T cell culture; TNF-α secretion; Tumor-reactive T cells